Characteristics of the implementation of a Pediatric Pneumology Reception Committee at a comprehensive health service provider in Montevideo (Archives of Pediatrics of Uruguay, 2020)
Introduction: pediatricians have an essential role in managing children with chronic respiratory disorders. Consultation with specialists is necessary in specific cases of uncertain diagnoses or in difficult to treat or severe cases. Protocol devising or training teams enable the selection of those requiring specialist care. Based on these criteria, a Pediatric Pneumology Reception Committee (PPRC) was created at a comprehensive health care provider in Montevideo.Objective: to describe the PPRC experience from 10/1/2017 to 09/30/2018Materials and methods: descriptive, retrospective study. Variables: age, sex, growth, reason for consultation, diagnosis, severity, death risk factors, comorbidities, vaccines, behavioral response, hospitalizations before and after intervention of the PPRC.Results: 306 children received care: 84% had asthma, 16% recurrent wheezing. 16% were 10 years of age. 21% had co-morbidities, with a predominance of recurrent wheezing (p
Keywords: Asthma; Pulmonology; Child